ANALYSIS OF SUPERVISORS’ PERFORMANCE IN APPLYING THEIR MAIN RESPONSIBILITIES AND FUNCTIONS IN ELEMENTARY - Muhamad Zaini; Nashuddin Nashuddin; Wildan Wildan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper reports the performance of supervisors in terms of their main duties, functions, and roles in elementary schools. The research uses a qualitative approach. Data were collected through interviews, observation, and documentation. The research location was at Cluster VII, Kopang sub-district in Central Lombok. Informants in the research involved school supervisors, school principals, teachers, operators, and the Educational Government Office. The results of the research indicate the performance of supervisors is seen from the main tasks of supervisors in elementary school at Cluster VII Kopang that is carried out through several stages of activities. They are compiling and implementing a supervisory program, evaluating the results of program implementation, and conducting professional guidance and training for teachers and or school principals. The role of supervisors seen from their performance is to monitor learning planning and conduct coaching and training for teachers and school principals. The main duty of supervisors based on factors that have an impact on their performance is to supervise, either academically or managerially. The role of supervisors based on factors that have an impact on their performance is that there are supporting and inhibiting factors in applying their role as school supervisors. Supporting factors look like a good response from principals, teachers, and other staff in the school. While the inhibiting factor is that there are still teachers who are afraid to get a supervisor’s supervision because of the lack of preparation for learning administration they have.